Histology and ultrastructure of glands associated with the sting apparatus of the swarm-founding wasp Protopolybia exigua (Hymenoptera: Vespidae: Polistinae) - da Silva, Marjorie [UNESP]; Noll, Fernando Barbosa [UNESP]; Billen, Johan (Elsevier, 2022)
Social insects present a great diversity of exocrine glands, which are linked to fundamental roles of social life, and their morphological characterization represents the first step toward the knowledge of their function. We here describe the exocrine glands present in the sting apparatus of queens and workers of the wasp Protopolybia exigua. Histological analysis of serial sections under light microscopy revealed a glandular epithelium in the spiracular plate, the quadrate plate, and the gonostyli, while the last two in addition also contain clusters of class-3 cells. A big cluster of class-3 cells was also found in the oblong plate of some workers and queens. These findings reveal that a variety of glands, in addition to the common venom gland and Dufour gland, are present in association with the sting apparatus, of which three glands are novel reports for the exocrine repertoire of social insects. The position of the glands suggests a role in lubrication to provide mobility of the sting and venom ejection and/or participation in alarm behavior, while a function related to reproduction is also possible. The peculiar characteristics displayed by swarm-founding wasps are linked with exocrine gland secretions, making their investigation in Epiponini wasps a vast and interesting field.
Keywords: Epiponini; Epithelial quadrate plate gland; Epithelial spiracular plate gland; Exocrine glands; Internal oblong plate gland; Social wasps